Impact of violacein from Chromobacterium violaceum on the mammalian gut microbiome - Pauer, Heidi; Pires Hardoim, Cristiane Cassiolato [UNESP]; Teixeira, Felipe Lopes; Miranda, Karla Rodrigues; Barbirato, Davi da Silva; Carvalho, Denise Pires de; Martha Antunes, Luis Caetano; Costa Leitao, Lvaro Augusto da; Lobo, Leandro Araujo; Cavalcanti Pilotto Domingues, Regina Maria (Public Library Science, 2018)
Violacein is a violet pigment produced by Chromobacterium violaceum that possesses several functions such as antibacterial, antiviral, antifungal, and antioxidant activities. The search for potential compounds and therapies that may interfere with and modulate the gut microbial consortia without causing severe damage and increased resistance is important for the treatment of inflammatory, allergic, and metabolic diseases. The aim of the present work was to evaluate the ability of violacein to change microbial patterns in the mammalian gut by favoring certain groups over the others in order to be used as a therapy for diseases associated with changes in the intestinal microflora. To do this, we used male Wistar rats, and administered violacein orally, in low (50 mu g/ml) and high (500 mu g/ml) doses for a month. Initially, the changes in the microbial diversity were observed by DGGE analyses that showed that the violacein significantly affects the gut microbiota of the rats. Pyrosequencing of 16S rDNA was then employed using a 454 GS Titanium platform, and the results demonstrated that higher taxonomic richness was observed with the low violacein treatment group, followed by the control group and high violacein treatment group. Modulation of the microbiota at the class level was observed in the low violacein dose, where Bacilli and Clostridia (Firmicutes) were found as dominant. For the high violacein dose, Bacilli followed by Clostridia and Actinobacteria were present as the major components. Further analyses are crucial for a better understanding of how violacein affects the gut microbiome and whether this change would be beneficial to the host, providing a framework for the development of alternative treatment strategies for intestinal diseases using this compound.